Munīrī Bosnawī and His Universal Geography Sab‘iyyât - Bušatlić, Ismet (Prilozi za orijentalnu filologiju, 2017)
Nürullâh šayh Ibrâhîm-efendi b. Iskandar al-Munîrî al-BosnawI al- Belgrâdî, mudarris, wa‘iz and muftl, author of several juridical, historical, geographical, and poetic works. The date of his birth is unknown (about 959/1551) and the place (at Bosnia) uncertain. He died at Belgrade about 1026/1617, but this date is not absolutely certain. The only information we have on his life is provided by the few lines inserted by Hağğl Hallfa in his Kašf al-zunün and reproduced by the other sources. His fame rests on an excellent work entitled Sab‘iyyât, whose text had been unknown ither. The manuscript appaered in the Ghazi Husrev-Bey's Library in Sarajevo, No. R-2640, f. 39-52. It is a short compendium in sixteen chapters. The work of Münir! was based on the Greek system of iqllms and represented the trend of rapprochement between astronomical and descriptive geography. The total geographical information acquired from contemporary as well as earlier Greek or Arab sources was classified according to the relevant sections - to the seven climates of Ptolemy. It also gives the latitudes and longitudes of many places which facilitates their reconstruction into a map. The work was an important contribution to phisical and descriptive geography.